Pengaruh Persepsi Resiko Dan Dan Gaya Hidup Konsumtif Terhadap Minat Fintech Lending Dengan Kemudahan Akses Sebagai Variabel Moderasi Di Kecamatan Prigen Pasuruan - Puteri Ayu Nabila; Miftahul Huda (JURNAL MANAJEMEN PENDIDIKAN, 2025)
The Effect of Risk Perception and Consumptive Lifestyle on Fintech Lending Interest with Ease of Access as a Moderation Variable in Prigen Pasuruan District The main problem in the use of fintech lending is how risk perception and a consumptive lifestyle affect public interest in online loan applications, especially in Prigen District, Pasuruan. This study aims to analyze the influence of these two variables on the interest in using fintech lending, with ease of access as a moderating variable. This study uses a quantitative approach with a survey method on 96 respondents who are active users of online loan applications. The analysis was carried out using Moderated Regression Analysis (MRA) through WarpPLS 7.0 software. The results show that risk perception and a consumptive lifestyle have a positive and significant effect on fintech lending interest. This means that despite the risks, convenience and benefits still attract user interest. A consumptive lifestyle also encourages impulsive use of fintech lending. However, ease of access is proven to negatively moderate the relationship between a consumptive lifestyle and interest, so too easy access can reduce the influence of a consumptive lifestyle. Meanwhile, ease of access does not moderate the relationship between risk perception and interest. This study recommends that fintech service providers place more emphasis on risk education and responsibility in using the service.